KAJIAN PEMBERDAYAAN BERBASISKAN KEWIRAUSAHAAN DALAM MENDUKUNG PROSES SUKSESI PADA AGRIBISNIS HORTIKULTURA - CHARINA, ANNE; HAPSARI, HEPI; MUKTI, GEMA WIBAWA; ANDRIANI, RANI (Jurnal Social Economic of Agriculture, 2015)
Indonesia's agricultural sector is still faced with a variety of problems, especially with regard to the low interest of youth to work in the agricultural sector. Total population aged 15 years and over who worked in the field of business in agriculture, plantation, forestry, and hunting in February 2013 amounted to 3,642,008 people, or 19.61% of the entire working population. This value certainly is not comparable if we see that our country is an agricultural country where agriculture is a major sector in Indonesia. In fact, to achieve better agricultural conditions required the participation of the younger generation as the successor to the farmer. The process of succession in agribusiness is very important to note.The purpose of this study to analyze the process of succession in agribusiness chili in Taraju, see the changes that occurred after reviewing succession and empowerment-based entrepreneurship which is believed to support the success of the process of succession in the agri-horticulture. This study will be conducted in the District. Taraju, Kab.Tasikmalaya using qualitative design and engineering case studies. Soft Systems Approach Methodhology (SSM) will be used to design an appropriate model. The results showed that the succession managed to farmers with large-scale enterprises because generally they have planned succession process, but on a small scale farmers they do not prepare the succession process. Agribusiness chili after a succession of changes to the packaging and marketing. Empowerment needs to be given to the first generation to be able to design a succession process as early as possible, while at empowering the next generation should be given to improving the business life, as well as generate interest in youth to businesses in the agricultural sector.